Prophylactic tenofovir alafenamide for hepatitis B virus reactivation and reactivation‐related hepatitis. Issue 2 (10th January 2023) - Suda, Goki; Baba, Masaru; Yamamoto, Yoshiya; Sho, Takuya; Ogawa, Koji; Kimura, Megumi; Hosoda, Shunichi; Yoshida, Sonoe; Kubo, Akinori; Fu, Qingjie; Yang, Zijian; Tokuchi, Yoshimasa; et al.
Abstract: No prospective study on the efficacy of tenofovir alafenamide (TAF), a novel tenofovir prodrug, in preventing hepatitis B virus (HBV) reactivation has yet been reported. This multicenter prospective study enrolled HBV‐carriers who received TAF to prevent HBV reactivation before antitumor or immunosuppressive therapy, and patients with resolved HBV infection who experienced HBV‐reactivation and received TAF to prevent HBV reactivation‐related hepatitis. The efficacy of prophylactic TAF in preventing HBV reactivation and HBV reactivation‐related hepatitis was evaluated at 6 and 12 months after initiating TAF. Overall, 110 patients were administered TAF to prevent HBV reactivation or HBV reactivation‐related hepatitis. Three patients died owing to primary disease, whereas one patient was transferred to another hospital within 6 months after initiating TAF. Seven patients died due to primary disease, and five patients were transferred to another hospital within 12 months after initiating TAF. Therefore, 106 and 94 (77 patients with HBV infection, 17 with previous‐HBV infection) patients were evaluated at 6 and 12 months after initiating TAF, respectively. No patient experienced HBV reactivation, HBV reactivation‐related hepatitis, or treatment discontinuation due to HBV reactivation or adverse events of TAF after 6 and 12 months. TAF could effectively prevent HBV reactivation and HBV reactivation‐related hepatitis. Lay Summary: Hepatitis B virus (HBV) reactivation during antitumor or immunosuppressive therapy could be fatal. Tenofovir alafenamide (TAF) is a novel prodrug of tenofovir with high efficacy and safety for hepatitis B infection. Nonetheless, there exist no prospective studies on the efficacy of TAF prophylaxis for the prevention of HBV reactivation. This prospective multicenter study is the first to show the high efficacy of TAF prophylaxis for the prevention of HBV reactivation.